The role of obstacles to innovation on innovative activities: An empirical analysis - Andrés Zahler; Daniel Goya; Matías Caama\~no (Inter-American Development Bank (IDB), 2018)
We study the effect of different types of barriers to innovation (financial, demand, knowledge, market, cooperation, and regulatory barriers) on firm level innovation inputs and outputs. Using a pooled sample of three Chilean innovation surveys, based on an instrumental variables approach, we find that the probability of generating innovation outcomes is signficantly reduced by demand and financial barriers. Regarding inputs for innovation, we find a clear negative relationship between financial and demand obstacles and the propensity to incur (non-R&D) innovation expenditures, but not with its intensity. We also provide evidence of heterogeneous effects across sectors, finding that knowledge obstacles are relevant for manufacturing and market structure obstacles for services, while demand and financial obstacles appear to matter across the board.
Keywords: D22; O31; O32; 330; Financial and non-financial barriers to innovation; sectoral heterogeneity in innovation barriers; potential innovators; instrumental variables